PLANEACIÓN FINANCIERA EN EL AUTOSERVICIO MEGA SHOP DE LA CIUDAD DE CATACOCHA, PERIODO 2018 – 2022 - Yaguana Díaz, Jessica Marcela (2019)
This designated thesis work: "FINANCIAL PLANNING IN THE MEGA SHOP SELF-SERVICE OF THE CITY OF CATACOCHA, PERIOD 2018 – 2022"; was developed on the basis of the stated objectives, which were met at the conclusion of the Financial Planning process applied in the Company. To meet both general and specific objectives, Financial Planning was carried out in the Mega Shop Self-Service in the city of Catacocha, for the period 2018 – 2022; where the collection of financial statement information from 2017 began, thus developing the vertical analysis and subsequent application of the financial indicators, with the aim of knowing the economic performance of the company, as well as the development of the financial plan, which contains the financial strategies and decisions to be implemented. Sales and purchase forecasts for the 2018 – 2022 periods were then developed, based on historical monthly sales and purchase data for the period December 2016 to December 2017 self-service, its preparation was made using the method of percentage of sales, starting with obtaining the difference in sales between the current month and the previous month, another of the parameters is the percentage, where the difference obtained is divided for the sales reached in the previous month; monthly sales 6 forecasts are developed as the percentage increase is made by actual sales. The same procedure is done to obtain the forecasts of the purchases. With the forecasts you were able to know the acquisition needs, increases and decreases that you get in each month. In terms of sales and purchases in 2019, a 5% increase was made in order to earn higher sales revenues, as was raised in the financial plan. Subsequently, the cash budget is presented, for which it is based on the cash inflows and outflows programs, which were also determined on the basis of the percentage of sales projected in the forecasts. These programs were able to develop and support the Cash Budget, reflecting that the company will not be short-deficit. Finally, the Proforma Financial Statements were made, which were developed on the basis of the 2017 Financial Statements, demonstrating the income and expenses for the following years, as well as the financial position expected at the end of the forecast period , their development was based on the application of the percentage of sales method, with the exception of staff costs, these were determined through the wage percentage, taking as reference the unified basic salary, to complete the thesis work was developed the equilibrium point of the projected years, where you could analyze the profitability that the company will be able to obtain, based on its level of sales covering its total costs. After the procedure has been carried out, it can be pointed out that the company's collection and payment policies do not coincide with the analysis of the cash conversion cycle; In this analysis it shows that receivables are collected every 147 days, while debts incurred with suppliers are canceled every 4 days.